ENHANCING SUSTAINABLE DEVELOPMENT IN UZBEKISTAN THROUGH TOURISM CLUSTERS (Modern education and development, 2024)
This paper examines the potential of tourism clusters in Uzbekistan to foster economic growth and sustainability within the tourism sector. By leveraging the country’s rich cultural heritage and historical cities like Samarkand and Bukhara, tourism clusters could enhance regional development, improve the visitor experience, and create new economic opportunities. Drawing on global examples, such as Costa Brava and Thailand, the paper explores the benefits and challenges of implementing such clusters, including infrastructure gaps and the need for skilled professionals. It also proposes strategies for overcoming these challenges through public-private partnerships and government initiatives, positioning Uzbekistan as a competitive, sustainable tourism destination.